Effects of dietary chlorogenic acid on growth, flesh quality and serum biochemical indices of grass carp (Ctenopharyngodon idella). (30th January 2017) - Sun, W.T.; Li, X.Q.; Xu, H.B.; Chen, J.N.; Xu, X.Y.; Leng, X.J.
Abstract: The study was to investigate effects of dietary chlorogenic acid (CGA) on growth performance, flesh quality and serum biochemical indices of grass carp (95.1 ± 0.3 g) ( Ctenopharyngodon idella ) fed seven different diets, including control diet, Eucommia ulmoides (EU)‐supplemented diet (20 g kg –1 ) and CGA‐supplemented diets containing 100, 200, 400, 600 and 800 mg/kg CGA. Contents of collagen and alkaline‐insoluble collagen in muscle and skin were significantly increased by dietary CGA and EU ( p < .05). Total essential amino acids (TEAA) and total amino acids (TAA) in muscle of grass carp fed EU diet or 400, 600 and 800 mg/kg CGA diet were significantly higher than those of fish fed control diet and 100 and 200 mg/kg CGA diet ( p < .05). Fish fed 200–800 mg/kg CGA showed significantly lower muscle crude lipid content than EU, control and 100 mg/kg CGA groups ( p < .05). Fish fed CGA‐supplemented diets (100–800 mg/kg) had significantly higher muscle fibre density and lower muscle fibre diameter than control group ( p < .05). In conclusion, supplementation of CGA improved flesh quality of grass carp, and supplemental level of CGA for improving flesh quality and growth was estimated to be 400 mg/kg diet.